MODEL KELAS EFEKTIF DAN MENYENANGKAN DALAM PEMBELAJARAN BAHASA ARAB ANAK USIA DINI - Tamaji, Sampiril Taurus; Kusno, Moh; Huda, Khusnul (Universitas Islam Darul Ulum, 2024)
The aim of writing this article is to explain an effective and enjoyable class model in early childhood Arabic language learning. To achieve learning success, teachers or formal school institutions need to prepare all students' learning needs, including a fun learning model in learning Arabic. In this article the author uses qualitative descriptive research, namely by presenting a complete picture in verbal or numerical form and presenting basic information about a relationship and exploring a phenomenon and social reality. Based on the discussion that has been written, the author provides an outline that an effective and enjoyable class is a place where a group of students gather to take part in learning activities that are well managed to achieve learning goals in a conducive atmosphere and without coercion. To achieve maximum learning goals, the class must be managed well and have an atmosphere that is able to support the teaching and learning process well. One of them is by making classes effective and fun. With a class atmosphere like this, the delivery will be better understood by students.